The Influence Of Financial Literacy Levels On Financial Management Among Housewives In Balangdatu, Tanakeke Islands District, Takalar Regency - Nurlia, Nurlia; Nasrullah, Nasrullah; Abd. Khaliq (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to determine the influence of the level of financial literacy on financial management among housewives. The method used in this research is quantitative. This research used 108 respondents with data collection techniques using the Solvin technique. The independent variable in this research is financial literacy, while the dependent variable is financial management. The data collection technique uses a questionnaire (Likert scale). The data analysis technique used is simple linear regression analysis. To strengthen the questionnaire data, validity and reliability tests were carried out. The normality test, heteroscedasticity test, and auto correlation test are used to provide certainty that the data held is unusual. Hypothesis testing in this research uses the t-test (partial) and the coefficient of determination (R). The results of this research show that financial literacy has a positive and significant influence on financial management among housewives in Balangdatu, Tanakeke Islands District, Takalar Regency.